Analisis Pengaruh Kualitas Website Terhadap Keputusan Pembelian di Usaha Mikro Kecil Menengah - -, Rafi Sulthan Rahman Majid (Asosiasi Ahli Administrasi Indonesia, 2022)
This study aims to determine the effect of website quality on buying decisions in various groups. Respondents came from people who actively online with minimum requirement of one hour. And people who have ties with author, such as friends, relatives, neighbours, etc. This study uses quantitative descriptive methods, validity and reliability tests, normality tests, and data analysis using simple linear regression. The sample in this study were 112 respondents. Data was collected by distributing questionnaires to respondents via Google Form. The results showed that the quality of website have a very significant effect on buying decision. This means, quality of website can improve buying decision.